1983
DOI: 10.1056/nejm198305053081802
|View full text |Cite
|
Sign up to set email alerts
|

Prekallikrein Activation and High-Molecular-Weight Kininogen Consumption in Hereditary Angioedema

Abstract: Patients with hereditary angioedema lack C-1 inhibitor, a plasma alpha 2-glycoprotein that inhibits both the proteolytic action of C1, the activated first component of the complement system, and the activity of components of the contact phase of coagulation: kallikrein, factor XIa, and factor XIIa. Such patients have been shown to have low levels of C4 and C2, the natural substrates for C-1, but the levels were not correlated with the presence of symptoms. We studied three patients with angioedema for evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(90 citation statements)
references
References 31 publications
7
83
0
Order By: Relevance
“…Loss of control over any of these levels may have severe pathophysiological consequences. For example, deficiency in C1 inhibitor, the major PKa inactivator, is associated with hereditary angioedema, a life-threatening condition with recurrent attacks of edema (16,57,58). The central role of bradykinin in the pathology of this disease has recently been proven by an elegant mouse model, in which targeted deletion of the C1 inhibitor gene resulted in spontaneous vascular leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of control over any of these levels may have severe pathophysiological consequences. For example, deficiency in C1 inhibitor, the major PKa inactivator, is associated with hereditary angioedema, a life-threatening condition with recurrent attacks of edema (16,57,58). The central role of bradykinin in the pathology of this disease has recently been proven by an elegant mouse model, in which targeted deletion of the C1 inhibitor gene resulted in spontaneous vascular leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinin causes vasodilation and increased vascular permeability, and since kininogens are consumed during attacks of hereditary angioedema, it has been suggested that kinins, including bradykinin, are responsible for this condition (Schapira et al, 1983). Patients undergoing treatment with ACE inhibitors may develop angioedema (Wood et al, 1987) which characteristically appears shortly after starting treatment.…”
Section: Introductionmentioning
confidence: 99%
“…30 Incubation of HAE plasma ex vivo was shown to generate bradykinin. 31,32 Furthermore, the contact system is activated in vivo during attacks of angioedema in HAE patients, [33][34][35] and increased levels of bradykinin have been measured in plasma during attacks of angioedema. 36 Contact system activation was also shown to cleave C1 inhibitor into a nonfunctional form, 11 and the plasma level of cleaved nonfunctional C1 inhibitor is increased during attacks of angioedema in HAE patients.…”
Section: What Is the Primary Mediator Of Swelling In Hae?mentioning
confidence: 99%